Comparative efficacy and safety of vedolizumab and infliximab in ulcerative colitis after failure of a first subcutaneous anti‐TNF agent: a multicentre cohort study. Issue 9 (22nd March 2020) - Hupé, Marianne; Rivière, Pauline; Nancey, Stephane; Roblin, Xavier; Altwegg, Romain; Filippi, Jerome; Fumery, Mathurin; Bouguen, Guillaume; Peyrin‐Biroulet, Laurent; Bourreille, Arnaud; Caillo, Ludovic; Simon, Mireille; et al.
Summary: Background: Few data exist to help select a second biologic agent in patients with refractory ulcerative colitis (UC). Aim: To compare the efficacy of infliximab (IFX) and vedolizumab (VDZ) in UC patients who failed a first subcutaneous anti‐tumor necrosing factor (TNF) agent. Methods: Consecutive UC patients from 12 French centres starting IFX or VDZ after at least one injection of adalimumab or golimumab have been included in a retrospective study. Outcomes were clinical remission at week 14, survival without treatment discontinuation and survival without UC‐related event. Results: Among the 225 patients included, clinical remission at week 14 was achieved in 40/154 (26%) patients treated with IFX and in 35/71 (49%) treated with VDZ ( P = 0.001). After a propensity score matching analysis, this difference remained significant (odds ratio: 1.67; 95% confidence interval: 1.08‐2.56; P = 0.02). With a median follow‐up of 117 weeks, survival rates without treatment discontinuation at years 1 and 3 were 50% and 29% with IFX, and 80% and 55% with VDZ, respectively ( P < 0.001). Regarding survival without UC‐related event, they were 49% and 27% with IFX, and 74% and 52% with VDZ ( P < 0.01). Conclusion: After failure of a first subcutaneous anti‐TNF agent, UC patients were more likely to achieve clinical remission with VDZ than those treated with IFX. Although due to prescription habits patients in the IFX group had a significantly more severe disease, these differences remained after adjustments and subgroup analyses. Such results have to be confirmed prospectively and warrant dedicated head‐to‐head trials.